Numerical simulations to assess the performance of scoop based lubrication devices for use in aero-engines - Prabhakar, Arun (2019)
In civil aircraft aero engine bearing chambers it is sometimes difficult to feed oil to bearings using the traditional under-race or targeted jet approaches. In such situations one proposed solution is that of a scoop delivery system. Published experimental investigations into scoop performance show that scoop collection efficiency (the percentage of oil delivered by the scoop system to its destination compared to that supplied by the feed jet) is a function of many operational and geometric parameters. However even with high speed imaging it is impossible to experimentally determine in detail the factors that most contribute to reduction in capture efficiency and it is here particularly that a Computational Fluid Dynamics (CFD) investigation has value.